Same words, different worlds? Living labs in multifunctional landscapes - Aligning terminologies, approaches for optimal research for impact - Staiger, Simone; Fuchs, Lisa Elena; Navarrete, Angela Patricia (2025)
Research for impact in the CGIAR Multifunctional Landscapes Program is implemented with partners and stakeholders in Living Labs. Living labs are gaining momentum as sub-national territories within which sustainable food system transformation is sought through multi-stakeholder engagement processes. According to the European Network of Living Labs (ENoLL), Living Labs are defined as “user-centered, open innovation ecosystems based on a systematic user co-creation approach, integrating research and innovation processes in real-life communities and settings”. In other words, Living Labs are intended to address complex situations and challenges requiring multi-scalar, multi-actor, multi-dimensional and holistic solutions.